The Occurrence of Malignancy in Trypanosoma brucei brucei by Rapid Passage in Mice - Cai, Xiao-Li; Li, Su-Jin; Zhang, Peng; Li, Ziyin; Hide, Geoff; Lai, De-Hua; Lun, Zhao-Rong (Frontiers in Microbiology, 2022)
Pleomorphic Trypanosoma brucei are best known for their tightly controlled cell growth and developmental program, which ensures their transmissibility and host fitness between the mammalian host and insect vector. However, after long-term adaptation in the laboratory or by natural evolution, monomorphic parasites can be derived. The origin of these monomorphic forms is currently unclear. Here, we produced a series of monomorphic trypanosome stocks by artificially syringe-passage in mice, creating snapshots of the transition from pleomorphism to monomorphism. We then compared these artificial monomorphic trypanosomes, alongside several naturally monomorphic T. evansi and T. equiperdum strains, with the pleomorphic T. brucei. In addition to failing to generate stumpy forms in animal bloodstream, we found that monomorphic trypanosomes from laboratory and nature exhibited distinct differentiation patterns, which are reflected by their distinct differentiation potential and transcriptional changes. Lab-adapted monomorphic trypanosomes could still be induced to differentiate, and showed only minor transcriptional differences to that of the pleomorphic slender forms but some accumulated differences were observed as the passages progress. All naturally monomorphic strains completely fail to differentiate, corresponding to their impaired differentiation regulation. We propose that the natural phenomenon of trypanosomal monomorphism is actually a malignant manifestation of protozoal cells. From a disease epidemiological and evolutionary perspective, our results provide evidence for a new way of thinking about the origin of these naturally monomorphic strains, the malignant evolution of trypanosomes may raise some concerns. Additionally, these monomorphic trypanosomes may reflect the quantitative and qualitative changes in the malignant evolution of T. brucei, suggesting that single-celled protozoa may also provide the most primitive model of cellular malignancy, which could be a primitive and inherent biological phenomenon of eukaryotic organisms from protozoans to mammals.